2016
DOI: 10.1103/physreve.93.042606
|View full text |Cite
|
Sign up to set email alerts
|

Analytic model for the electrowetting properties of oil-water-solid systems

Abstract: Analytic model for the electrowetting properties of oil-water-solid systems Cavalli, A.; Bera, B.; van den Ende, D.; Mugele, F.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Experimentally, the presence of such a film and the dependence of its thickness on the salinity of the brine has been reported recently by our team for a simplified system in the absence of surface active species. 21 In that work and in a subsequent theoretical study that included charge regulation, 37 it was possible to reproduce the experimentally observed salinity-dependent wetting transition within the DLVO theory by decomposing φ( h ) explicitly into its electrostatic, van der Waals, and (exponentially decaying) short-range hydration contribution by writing φ( h ) = φ el ( h ) + φ vdW ( h ) + φ h ( h ) with explicit expressions for each term. 21 The model and the complementary surface charge measurements confirmed that the alteration of the water contact angle from almost complete water wetting in the presence of Na + or K + to finite contact angles in the presence of Ca 2+ or Mg 2+ could be attributed to a reversal of the muscovite/water interfacial charge.…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally, the presence of such a film and the dependence of its thickness on the salinity of the brine has been reported recently by our team for a simplified system in the absence of surface active species. 21 In that work and in a subsequent theoretical study that included charge regulation, 37 it was possible to reproduce the experimentally observed salinity-dependent wetting transition within the DLVO theory by decomposing φ( h ) explicitly into its electrostatic, van der Waals, and (exponentially decaying) short-range hydration contribution by writing φ( h ) = φ el ( h ) + φ vdW ( h ) + φ h ( h ) with explicit expressions for each term. 21 The model and the complementary surface charge measurements confirmed that the alteration of the water contact angle from almost complete water wetting in the presence of Na + or K + to finite contact angles in the presence of Ca 2+ or Mg 2+ could be attributed to a reversal of the muscovite/water interfacial charge.…”
Section: Discussionmentioning
confidence: 99%
“…Adsorption fate of surfactant is the main concern in this type of production methods that limits the use/application of various surfactants for different oil reservoirs. A number of researchers have focused on this important issue 9 , 10 . For instance, Rodriguez 9 studied the adsorption of surfactants on carbonate rock samples taken from an oil reservoir in Saudi Arabia 9 .…”
Section: Introductionmentioning
confidence: 99%
“…According to the results, when the flow rate increases, the amount of adsorption will decrease. Besides the experimental works, several valuable analytical models have been developed to determine the adsorption behavior of surfactants from mathematical viewpoint 10 12 . Such models provide very deep understanding regarding adsorption phenomenon of surfactants onto the solid surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A subsequent more detailed modeling effort highlighted the role of charge regulation and short-range chemical forces for the exact value of the contact angles. 55…”
Section: Introductionmentioning
confidence: 99%